(untitled) (gjstudies, 2021)
This research investigates the nuanced relationship between concentrated ownershipstructures and the transparency of financial disclosures, challenging the conventionalprincipal-agent paradigm that predominantly views dispersed ownership as the primary driver of opaque reporting. We introduce a novel methodological framework thatsynthesizes concepts from information theory, specifically Shannon entropy and mutual information measures, with traditional corporate governance metrics to quantifydisclosure transparency not as a binary outcome but as a continuous spectrum of information quality and accessibility. Moving beyond the typical focus on institutionalor insider ownership percentages, our study constructs a multi-dimensional ’OwnershipInfluence Vector’ that captures the concentration, stability, and strategic alignment ofcontrolling blocks. Utilizing a hand-collected dataset of 450 firms across three distinctregulatory jurisdictions over a ten-year period, we employ a quasi-experimental designthat leverages exogenous regulatory shocks to ownership rules as natural experiments.Our results reveal a non-linear, context-dependent relationship: moderate ownershipconcentration, contrary to much existing literature, can act as a catalyst for superiortransparency when coupled with specific governance mechanisms, such as independent audit committees with financial expertise. However, at extreme concentrationlevels, transparency deteriorates significantly, supporting entrenchment hypotheses.Furthermore, we identify a previously under-explored ’transparency threshold’ effect,where the informativeness of disclosures increases up to a point of ownership cohesion, after which additional concentration yields diminishing informational returns.The study’s primary contribution lies in its original theoretical reconceptualizationof transparency as an information-theoretic property and its empirical demonstrationthat the ownership-transparency nexus is conditional on the interactive effects of control, incentive alignment, and external monitoring forces, rather than a simple linearfunction. These findings have profound implications for regulators aiming to designdisclosure regimes that account for the underlying ownership architecture of firms.